Sex Determination in Ceratopteris richardii Is Accompanied by Transcriptome Changes That Drive Epigenetic Reprogramming of the Young Gametophyte. Issue 7 (1st July 2018) - Atallah, Nadia M; Vitek, Olga; Gaiti, Federico; Tanurdzic, Milos; Banks, Jo Ann
Abstract: The fern Ceratopteris richardii is an important model for studies of sex determination and gamete differentiation in homosporous plants. Here we use RNA-seq to de novo assemble a transcriptome and identify genes differentially expressed in young gametophytes as their sex is determined by the presence or absence of the male-inducing pheromone called antheridiogen. Of the 1, 163 consensus differentially expressed genes identified, the vast majority (1, 030) are up-regulated in gametophytes treated with antheridiogen. GO term enrichment analyses of these DEGs reveals that a large number of genes involved in epigenetic reprogramming of the gametophyte genome are up-regulated by the pheromone. Additional hormone response and development genes are also up-regulated by the pheromone. This C. richardii gametophyte transcriptome and gene expression dataset will prove useful for studies focusing on sex determination and differentiation in plants.